“Nothing about politics”: The political scope in rural participatory governance, a case-study in the Basque Country, Spain - Patricia García-Espín (Journal of Deliberative Democracy)
Participatory mechanisms are understood as settings for citizens’ political engagement. However, participants frequently depict these institutions as nonpolitical. In this paper, the political scope of participatory institutions is examined through a case-study of town meetings (concejos abiertos) in the Basque Country (Spain). Through ethnographic observation and interviews with 53 participants, we analyze how participants deal with public issues, and how they limit or expand the political scope of their participation. In concejos, participants talk about “small deliberation” issues such as sewers or water installations. They reject partisan issues in their everyday engagement. However, they cultivate a culture of self-management, and embark on political campaigns on selective issues. The political scope of this institution is opened and closed by participants according to cultural and organizational conditions. In the end, small deliberation on community issues can be a basis for further engagement on broader political concerns. Small deliberation –if sustained over time- is not as small as it seemed initially.